Public health risks of multiple-drug-resistant Enterococcus spp. in Southeast Asia - Daniel, D.; Lee, S.; Dykes, Gary; Rahman, S. (2015)
Enterococci rank as one of the leading causes of nosocomial infections, such as urinary tract infections, surgical wound infections, and endocarditis, in humans. These infections can be hard to treat because of the rising incidence of antibiotic resistance. Enterococci inhabiting nonhuman reservoirs appear to play a critical role in the acquisition and dissemination of antibiotic resistance determinants. The spread of antibiotic resistance has become a major concern in both human and veterinary medicine, especially in Southeast Asia, where many developing countries have poor legislation and regulations to control the supply and excessive use of antimicrobials. This review addresses the occurrence of antibiotic-resistant enterococci in Association of Southeast Asian Nations countries and proposes infection control measures that should be applied to limit the spread of multiple-drug-resistant enterococci.